Programa de Gestão e Desempenho: o processo de implementação na Universidade Federal de Goiás - Santos, Regiane Miranda (2024)
The need for isolation during the COVID-19 pandemic consolidated remote work as a strategic tool for maintaining private and governmental operations, highlighting the importance of flexibility and efficiency in the public sector. In response to this need, the federal government regulated teleworking through the Performance and Management Program (PGD), established in 2022, with the goal of modernizing public management practices with a focus on efficiency and results delivery. This study investigates the implementation process of the PGD at the Federal University of Goiás (UFG), analyzing the challenges and benefits of performancebased management in public administration. The research examined the PGD pilot project at the university, conducted between February 2023 and August 2024, during its first two phases. The main objective was to explore the regulatory policy of the PGD at the federal level and its application at UFG, assessing the perception of the Pilot Project participants as key agents driving the institutional implementation process. The methodology employed was applied in nature, using a mixed methods approach that integrated qualitative and quantitative aspects. The qualitative analysis included documentary research and the evaluation of open-ended responses from a structured questionnaire, while the quantitative approach utilized descriptive statistics and cluster analysis techniques to examine the collected data. The results indicate that the pilot project brought benefits such as increased productivity, greater flexibility, and improved work-life balance, particularly in the telework modality. However, challenges such as inadequate training, difficulties in strategic planning, and bureaucratic resistance to adopting new practices still limit its full effectiveness. Additionally, it was observed that academic units and supplementary bodies with greater autonomy adapted better, while more traditional organizational structures faced difficulties in implementation. The relevance of this research lies in its contribution to the modernization of public management and the identification of best practices for the adoption of the PGD in Federal Higher Education Institutions (IFES). On a social level, the findings reinforce the need for more inclusive policies that value employee participation in building a more efficient and humanized work model. In the field of management, the results highlight the importance of decentralizing decision-making, offering continuous training, and strategically using technology to ensure the effective implementation of the program. As a practical contribution, this study presents a technical-technological product (PTT) with recommendations that can serve as a reference for other institutions seeking to improve performance-based management in the public sector